Transformational Leadership Practices in Saudi Arabia: A Case Study of the Saudi Telecom Industry - Alsalman , Asmahan Ibrahim (Journal of Ecohumanism, 2025)
This study explores the implementation and impact of transformational leadership practices within the Saudi telecom industry, a sector pivotal to the nation’s economic diversification efforts. Utilizing a qualitative case study technique, it examines how transformational leadership influences organizational performance, employee motivation, and innovation. Employing a mixed-methods approach, data were collected through interviews with 60 industry leaders and surveys of 300 employees across various telecom companies in Saudi Arabia. The findings reveal that transformational leadership practices are increasingly adopted in the Saudi telecom industry, promoting a culture of continuous improvement and adaptive change. Key practices identified include the articulation of a compelling vision, fostering an environment of trust and collaboration, and providing individualized support and encouragement. These practices not only enhance employee satisfaction and productivity but also drive the industry’s competitive edge in a rapidly evolving market. The study concludes with implications for leadership development programs in Saudi Arabia, emphasizing the need for culturally tailored strategies to optimize leadership potential and organizational success in the region.